Martin Luther [compact disc, unabridged] : the man who rediscovered God and changed the world - Metaxas, Eric (Penguin Audio, 2017)
"On All Hallow's Eve in 1517, a young monk named Martin Luther posted a document he hoped would spark an academic debate, but that instead ignited a conflagration that would forever destroy the world he knew. Five hundred years after Luther's now famous Ninety-five Theses appeared, Eric Metaxas...paints a startling portrait of the wild figure whose adamantine faith cracked the edifice of Western Christendom and dragged medieval Europe into the future...Luther's monumental faith and courage gave birth to the ideals of liberty, equality, and individualism that today lie at the heart of all modern life."--Container.